Implementation of Guided Inquiry Based On Contextual Approach to Improve Students Critical Thinking Skills on Reaction Rate Material - Bintari Catur Anjarwati; Harun Nasrudin (Universitas Negeri Yogyakarta, 2022)
The purpose of this study is to describe the improvement of students' critical thinking skills on the reaction rate material by implementing a guided inquiry based on a contextual approach. The subjects were students of class XI MIA 7 SMA Negeri 1 Gedangan with a one-group pretest-posttest research design. The methods used to collect data are observations, tests, and response questionnaires. The research instruments used were critical thinking skills test sheets, observation sheet of learning model implementation, students activity observation sheets, and students response questionnaires. Data analysis was carried out using quantitative techniques assisted by SPSS 23. The results showed that (1) The percentage of the implementation of the guided inquiry with a contextual-based approach at I and II meetings is 98.66% (very good) and 99.48% (very good). (2) The relevant activities of students at I meeting is 98.06% and at II meeting is 97.78%. (3) Students' critical thinking skills are successfully improved with an average gain score on the interpretation indicator is 0.85 (high), the inference indicator is 0.82 (high), the analysis indicator is 0.77 (high), and explanation indicator is 0.75 (high). (4) Students' positive response to the learning model implementation is 96.35% (very good). The results showed that students' critical thinking skills on the reaction rate material were successfully improved by implementing a guided inquiry learning model based on a contextual approach.